Sosialisasi Komisi Pemilihan Umum dalam Meningkatkan Partisipasi Pemilih pada Pemilihan Bupati dan Wakil Bupati Kabupaten Ciamis : Studi Kasus di Kecamatan Ciamis - Ersa Mitha Alutgusti (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This research is entitled "Socialization of the General Election Commission in Increasing Voter Participation in the 2024 Regent and Deputy Regent Election of Ciamis Regency (Case Study in Ciamis District)". The focus of this research is to determine how the implementation of socialization carried out by the General Election Commission (KPU) of Ciamis Regency in an effort to increase public participation in the 2024 Regent and Deputy Regent Election, especially in the Ciamis District area. The research method used is descriptive qualitative with a case study approach. Data collection techniques include in-depth interviews with related parties, direct observation of socialization activities, and collection of supporting documentation. The data obtained are analyzed qualitatively through the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Ciamis Regency KPU carried out socialization by referring to the Theory of Three Elements of Socialization proposed by Haryanto (2018) in the book Political Socialization: An Initial Understanding. The three elements include: Socialization Agents, namely parties who play a role in conveying information, such as KPU officers, District Election Committees (PPK), and community leaders, Socialization Materials, including information regarding election stages, voting procedures, the importance of voting rights, and the role of the community in maintaining democracy, Socialization Methods, which are carried out through face-to-face meetings, leaflet distribution, banner installation, social media, and community-based activities. Although socialization activities have been carried out in a planned manner and involved various media, research results indicate that their implementation has not been optimal. Some obstacles found include limited reach to all levels of society, minimal participation in socialization activities, and a lack of innovation in information delivery methods. In conclusion, the socialization carried out by the Ciamis Regency KPU for the 2024 Regent and Deputy Regent Election has been running but needs to be increased in intensity, creativity, and equal distribution of targets so that voter participation can be maximized.